Bacteriophage T4 Self-Assembly: Localization of gp3 and Its Role in Determining Tail Length - Vianelli, A. (American Society for Microbiology, 2000)
Gene 3 of bacteriophage T4 participates at a late stage in the T4 tail assembly pathway, but the hypothetical protein product, gp3, has never been identified in extracts of infected cells or in any tail assembly intermediate. In order to overcome this difficulty, we expressed gp3 in a high-efficiency plasmid expression vector and subsequently purified it for further analysis. The N-terminal sequence of the purified protein showed that the initial methionine had been removed. Variant C-terminal amino acid sequences were resolved by determining the cysteine content of the protein. The molecular mass of 20.6 kDa for the pure protein was confirmed by Western blotting, using a specific anti-gp3 serum for which the purified protein was the immunogen. We also demonstrated, for the first time, the physical presence of gp3 in the mature T4 phage particle and localized it to the tail tube. By finding a nonleaky, nonpermissive host for a gene 3 mutant, we could clearly demonstrate a new phenotype: the slow, aberrant elongation of the tail tube in the absence of gp3.